Validity and Reliability of The Perceived Stress Scale with RASCH Model - Arif Budi Prasetya; Diana Septi Purnama; Fajar Wahyu Prasetyo (Universitas Ahmad Dahlan, 2019)
The study aims to determine the validity and reliability of the perceived stress scale instrument. The study uses a quantitative approach. The respondents involved in this study were 195 undergraduate and master students of guidance and counseling at Yogyakarta State University. Respondents were determined through a simple random sampling technique—data analysis using the RASCH model. Based on the results of the analysis, it can be concluded that the Perceived Stress Scale has good quality, meaning that it meets the validity and reliability aspects. The results of the study can be used as an instrument of need assessment in guidance and counseling services.Keywords: perceived stress scale, RASCH model, need assessment